A MODEL OF ANALYSIS OF THE OCCUPATIONAL SAFETY AND HEALTH SYSTEM IN THE PRODUCTION SYSTEM - Vranješ, Biljana; Todić, Mladen (Journal of Applied Engineering Science, 2019)
The occupational health and safety system as an integral part of the organization of work includes a set of technical and organized measures and activities aimed at achieving safety at work, elimination and prevention of hazards/ harmfulness that can cause occupational injuries, occupational and other diseases and the protection of health and working capacity workers. The main goal of occupational health and safety is to reduce the number of accidents, injuries, occupational diseases and work-related illnesses. An efficient way of managing the occupational health and safety system is achieved by defining, monitoring and adjusting the performance indicators through a systemic and process approach. The modern concept of occupational safety implies that every worker sees himself as an active participant in the occupational safety system who can contribute to the achievement of his goals, but also the responsibility for the process of improving occupational safety for everyone in the organization. A model of analysis presented in this research enables workers to express their views on the elements of the occupational safety and health system in their organization. By applying this model, we can analyze the input elements related to the profile of workers that influence the acceptance and adoption of basic rules and occupational safety measures. The results of the analysis can be an important source of information in the process of knowledge management in the occupational safety system through the creation of measures to eliminate organizational and functional deficiencies.